5 - Restructuring the African State for more Effective Management of Globalisation: - Kiggundu Moses Ν. (Africa Development, 2022)
It is generally accepted that globalisation is here to stay and that Africa and the Africans need to participate gainfully and equitably in the global economy and global society. This paper investigates Africa's readiness for more effective globalisation. Drawing on indicators from both the macro (national) and micro (sub-national) levels, this paper concludes that Africa is individually and insti tutionally less ready for globalisation than other parts of the world. The paper makes conceptual and practical suggestions for rethinking, restructuring and reorganising the African state for better understanding and management of globalisation. Before undertaking specific reforms and capacity building initia tives, every country should develop a strong national foundation for globalisation involving, among other things, articulation of widely shared societal core val ues, institutions, competences and functions. Lack of nationally shared core values and a strategic sense of direction and institutional weaknesses at both the macro and micro levels combine to render the African state especially vulner able to the vagaries of globalisation.